Digital Literacy. An exercise for the construction of Peace from the Town of Suba (Bogotá, Colombia) - Díaz Vásquez, Rafael Francisco; Bejarano Pérez, Juan Pablo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2021)
Objective: The objective of this work was to propose the use of ICTs as a democratic strategy for the construction of Peace in Colombia, based on a case study. Originality/contribution: The project developed had as the start-up of a research process that has had stages from 2016 to 2019, financed by different institutions such as local entities (Local Mayor's Office of Suba, Project 240 of 2016), Fundación Tortuga, the Center for Society and Space Studies and the Grancolombiano Polytechnic, in which the incorporation of learning experiences outside the classroom through the use of ICT can be verified. Method: The work was developed through Participatory Action Research -IAP, with the population of the town of Suba, telling a series of experiences that allow establishing what are the uses, experiences and actions to be improved in terms of the use of Information Technologies. Information and Communication and access to electronic devices in a population sample, which allowed the development of a "Digital Literacy" process. Strategies/information collection: It is possible to collect information from national and local data on the use of ICT, as well as the collection of the data themselves by the project in the town of Suba, allowing to revalidate and in some cases the true ICT insertion within the population of a considerable sample of urban location strata. Conclusions: The analysis of results that is exposed includes the incorporation of learning experiences in the classroom, allowing to establish the uses of ICT, since the use of learning processes through the use of ICT, within the classroom, is generally considered. as a tool in teaching learning. In this case, the presentation of results and analysis presented understands how outside the classroom in Colombia, there is a large part of the population that can use ICTs for learning processes, for which it is necessary to establish processes that we call within our proposed as "Digital Literacy"